Operational queueing system in the scheme of diffusion approximation with evolution averaging - Mamonova, G. V. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We consider an operational queuing system of the type [SM | M | ∞]^N in the scheme of diffusion approximation. The queueing system is described by a semi-Markov random evolution.